F44 Differences in thermoregulation after exercise in huntington's disease. (12th September 2022) - Collazo, Carla; Soto-Célix, María; Raya-González, Javier; Castillo-Alvira, Daniel; Rodríguez-Fernandez, Alejandro; Rivadeneyra-Posadas, Jéssica; Simón-Vicente, Lucía; Calvo, Sara; Saiz-Rodriguez, Miriam; Fahed, Vitória S; Cubo, Esther; ,
Abstract : Background: Thermoregulation is the maintenance of a relatively constant core body temperature which influences tolerance to physical activity. Brown adipose tissue, skeletal muscle, and hypothalamus are components involved in this process. Transgenic animal models of Huntington's disease (HD) have provided informative models of thermoregulatory disturbances (TD), such as hypothermia, impaired adaptive thermogenesis and an altered circadian temperature rhythm. TD have been rarely reported in HD patients, but evidence from molecular, biochemical and structural studies suggest that TD may be underestimated. Aims: To evaluate the thermoregulation responses to physical activity in a HD cohort and the differences compared to healthy subjects. Methods: Nineteen HD patients from the Neurology Department of the Hospital Universitario de Burgos and 10 controls ( Table 1 ) were studied in a laboratory (University Isabel I, Burgos, Spain). Demographics, clinical and body composition by multifrequency bioimpedance (SECA mBCA 525, Hamburg, Germany) data were obtained. Pre and post physical activity (walking at different speeds and an incremental test on a treadmill, with an average duration of 30 minutes) body map thermography (FLIR E86-EST) was obtained. Results/Outcome: Pre and post, mean external temperature showed an inverse correlation with CAG repeats (r=-.63), and post-exercise temperature with fat mass (r=-.65). Comparing controls with HD patients, there was a higher decrease of temperature after physical activity (p=.01). Conclusions: Thermoregulation in HD is altered after exercise. Further studies are needed to understand the influence of thermoregulation on physical activity tolerance, to confirm these preliminary results.